2020
DOI: 10.1002/qre.2790
|View full text |Cite
|
Sign up to set email alerts
|

On increasing the sensitivity of moving average control chart using auxiliary variable

Abstract: In the statistical process control, the most useful tool to monitor the manufacturing processes in the industries is the control chart. Quality practitioners always desire the charting structure that identifies sustainable changes in the monitoring processes. The sensitivity of the control chart is improved when additional correlated auxiliary information about the study variable is introduced. The regression estimate in the form of auxiliary and supporting variables presents an unbiased and efficient statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Proposed control charts are compared with Refs. 47 , 33 , 51 , 44 , 9 , 25 . It is found that the proposed control chart performs better in detecting small shifts than all of these control charts.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed control charts are compared with Refs. 47 , 33 , 51 , 44 , 9 , 25 . It is found that the proposed control chart performs better in detecting small shifts than all of these control charts.…”
Section: Discussionmentioning
confidence: 99%
“…Although adaptive schemes were initially developed to be used in memory-less control charts, studies such as Perdikis & Psarakis 7 have shown that combining both approaches (using memory-type and adaptive control charts) further improves the chart’s sensitivity and performance. Nonetheless, there are also studies such as Amir et al 8 and Abbas et al 9 that have used auxiliary information to increase the sensitivity of memory-type control charts.…”
Section: Introductionmentioning
confidence: 99%
“…Abbas [10] introduced the double PM chart for detecting the small and medium changes in the process and showed that the proposed design perform sequentially well to its counterparts. The auxiliary information-based PM chart was created by Abbas et al ( 2019) [15], who also concluded that the suggested scheme is consistently superior to its rivals.…”
Section: Introductionmentioning
confidence: 99%